2022
DOI: 10.1007/s00247-022-05324-8
|View full text |Cite
|
Sign up to set email alerts
|

Organ doses in preterm and full-term neonates and infants — a retrospective study on 1,064 chest radiographs

Abstract: Background Chest radiography is the most frequent X-ray examination performed in the neonatal period. However, commonly used dosimetric entities do not describe the radiation risk sufficiently. Objective The aim of this study was to investigate selected organ doses and total body dose of chest radiographs in preterm and full-term neonates and infants. Materials and methods In this retrospective study, we evaluated 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In line with the ALARA (as low as reasonably achievable) principle, radiographic technique should be optimized to minimize exposure to ionizing radiation while maintaining diagnostic accuracy, including proper collimation (especially given the small size of neonates and infants), and standardized exposure indices to minimize “dose creep” phenomenon in digital radiography 1,2 . Radiation doses vary across facilities, but Kammer and colleagues in 2022 recently concluded that the mean entrance dose to neonates and infants remains in a low range between 15 and 25 µGy 3–5 . Contrary to the standard posteroanterior and lateral view protocol for outpatients, single portable anteroposterior view radiographs are most commonly obtained in the NICU.…”
Section: Imaging Modalities and Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the ALARA (as low as reasonably achievable) principle, radiographic technique should be optimized to minimize exposure to ionizing radiation while maintaining diagnostic accuracy, including proper collimation (especially given the small size of neonates and infants), and standardized exposure indices to minimize “dose creep” phenomenon in digital radiography 1,2 . Radiation doses vary across facilities, but Kammer and colleagues in 2022 recently concluded that the mean entrance dose to neonates and infants remains in a low range between 15 and 25 µGy 3–5 . Contrary to the standard posteroanterior and lateral view protocol for outpatients, single portable anteroposterior view radiographs are most commonly obtained in the NICU.…”
Section: Imaging Modalities and Techniquesmentioning
confidence: 99%
“…1,2 Radiation doses vary across facilities, but Kammer and colleagues in 2022 recently concluded that the mean entrance dose to neonates and infants remains in a low range between 15 and 25 µGy. [3][4][5] Contrary to the standard posteroanterior and lateral view protocol for outpatients, single portable anteroposterior view radiographs are most commonly obtained in the NICU. Additional projections can be considered based on the clinical question or prior imaging: for example, a lateral view may be helpful for the assessment of pleural effusions or pneumothoraces, and lateral decubitus views and/or expiratory images can be evaluated for air trapping.…”
Section: Radiographymentioning
confidence: 99%